2004
DOI: 10.1093/humrep/deh182
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of iron deposition in endometriotic lesions induced in the nude mouse model

Abstract: Iron conglomerates, typically found in the stroma of endometriotic lesions, were induced by erythrocytes present in menstrual effluent. This may be one of the factors triggering oxidative damage and chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…In the presented study, a higher concentration of iron was observed in PF of women suffering from endometriosis, compared to the reference groups. These results are in accordance with those obtained by other authors [5,22,23,24]. It was also noted that the concentration of iron in PF of women in advanced stages of endometriosis was higher, compared to patients suffering from stage I of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…In the presented study, a higher concentration of iron was observed in PF of women suffering from endometriosis, compared to the reference groups. These results are in accordance with those obtained by other authors [5,22,23,24]. It was also noted that the concentration of iron in PF of women in advanced stages of endometriosis was higher, compared to patients suffering from stage I of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…Van Langendonckt et al showed that the presence of an increased number of erythrocytes derived from menstrual blood within the peritoneal cavity may have implications for the development of endometriotic lesions. The number of endometriotic lesions induced in nude mice tended to be larger when unfractionated menstrual effluent rather than menstrual endometrium, either alone or in combination with erythrocytes or serum, was injected [8]. In our immunocompetent mouse model, the Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Nisolle et al [7] observed attachment between human transplants and the peritoneum of nude mice on day 1. Van Langendonckt et al [8] reported that iron conglomerates typically found in the stroma of endometriotic lesions in nude mice were induced by erythrocytes in human menstrual effluent. As a syngeneic mouse model using an immunocompetent mouse, Somigliana et al [9] first demonstrated the growth of endometrial tissues in the peritoneal cavity of C57BL/6 or BALB/c three weeks after the injection of syngeneic endometrial fragments; however, to the best of our knowledge, little attention has been given to the role of blood brought into the peritoneal cavity at the time of early endometrial-peritoneal interactions in immunocompetent mice.…”
Section: Introductionmentioning
confidence: 99%
“…An iron-enriched diet significantly increased the incidence of colorectal tumors in a mouse ulcerative colitis model (43). Thus, iron induces carcinogenesis in many organs and several reports have indicated the role of iron in the pathogenesis of endometriosis (44,45), but as far as we know, there is no report suggesting the role of iron in carcinogenesis from endometriotic cysts.…”
Section: Discussionmentioning
confidence: 99%